HYDRIDE4MOBILITY: An EU HORIZON 2020 project on hydrogen powered fuel cell utility vehicles using metal hydrides in hydrogen storage and refuelling systems. (19th October 2021) - Yartys, Volodymyr A.; Lototskyy, Mykhaylo V.; Linkov, Vladimir; Pasupathi, Sivakumar; Davids, Moegamat Wafeeq; Tolj, Ivan; Radica, Gojmir; Denys, Roman V.; Eriksen, Jon; Taube, Klaus; Bellosta von Colbe, Jose; Capurso, Giovanni; et al.
Abstract: The goal of the EU Horizon 2020 RISE project 778307 "Hydrogen fuelled utility vehicles and their support systems utilising metal hydrides" (HYDRIDE4MOBILITY), is in addressing critical issues towards a commercial implementation of hydrogen powered forklifts using metal hydride (MH) based hydrogen storage and PEM fuel cells, together with the systems for their refuelling at industrial customers facilities. For these applications, high specific weight of the metallic hydrides has an added value, as it allows counterbalancing of a vehicle with no extra cost. Improving the rates of H2 charge/discharge in MH on the materials and system level, simplification of the design and reducing the system cost, together with improvement of the efficiency of system "MH store-FC", is in the focus of this work as a joint effort of consortium uniting academic teams and industrial partners from two EU and associated countries Member States (Norway, Germany, Croatia), and two partner countries (South Africa and Indonesia). The work within the project is focused on the validation of various efficient and cost-competitive solutions including (i) advanced MH materials for hydrogen storage and compression, (ii) advanced MH containers characterised by improved charge-discharge dynamic performance and ability to be mass produced, (iii) integrated hydrogen storage and compression/refuelling systems which are developed and tested together with PEM fuel cells during the collaborative efforts of the consortium. This article gives an overview of HYDRIDE4MOBILITY project focused on the results generated during its first phase (2017–2019). Highlights: Advanced metal hydrides for H storage and compression were proposed. MH containers with improved H charge-discharge dynamic performance. Integrated with PEM fuel cell hydrogen energy system was developed. EU Horizon 2020 RISE project 778307 project HYDRIDE4MOBILITY. Hydrogen powered forklift uses MH based H storage and PEM fuel cell.